2008
DOI: 10.1063/1.2909150
|View full text |Cite
|
Sign up to set email alerts
|

Configurational, electronic entropies and the thermoelectric properties of nanocarbon ensembles

Abstract: Reaction of disperse ultrananocrystalline diamond ͑UNCD͒ and mixtures of UNCD containing 10%-20% nanoboron carbide ͑B 4 C͒ with methane gas at temperatures near 1200 K results in mechanically rigid compacts called nanocarbon ensembles ͑NCE͒ and boron-doped NCE, respectively. Seebeck coefficient and electrical conductivity results lead to strongly temperature dependent power factors that increase 30-40 fold for boron containing ensembles compared to undoped material. It is likely that boron substitutional dopin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…In the trend of |α| ( Figure 2 b), a broad maximum can be seen slightly below to the equiatomic composition, close to the composition of the highest chemical disorder, a similar situation to that of other entropic parameters of such alloys [ 31 ], but a shoulder at a composition of about 70 at.%-Ni is also evident. This observation of high |α|for a high chemical disorder reflects the general finding that high configurational entropy is a prerequisite for the observation of large |α| [ 32 ]. Because of the close relationship between large |α| and high configurational entropy, it was recently suggested to even use configurational entropy as a gene-like performance indicator for the computational search of new thermoelectric materials [ 33 ].…”
Section: Resultssupporting
confidence: 60%
“…In the trend of |α| ( Figure 2 b), a broad maximum can be seen slightly below to the equiatomic composition, close to the composition of the highest chemical disorder, a similar situation to that of other entropic parameters of such alloys [ 31 ], but a shoulder at a composition of about 70 at.%-Ni is also evident. This observation of high |α|for a high chemical disorder reflects the general finding that high configurational entropy is a prerequisite for the observation of large |α| [ 32 ]. Because of the close relationship between large |α| and high configurational entropy, it was recently suggested to even use configurational entropy as a gene-like performance indicator for the computational search of new thermoelectric materials [ 33 ].…”
Section: Resultssupporting
confidence: 60%
“…The Seebeck coefficient exceeds 100 lV K À1 in all foils at high temperature, leading to decent power factors exceeding 0.1 mW m À1 K À2 . Unlike other carbon-based materials, such as graphite [68], nanocarbon ensembles [69] or graphitic boron carbon nitride (BC 3 N) [70], diamond achieves a considerable Seebeck coefficient. From its temperature dependence a metal-like transport is concluded for our foils, whereas the dependence of the electrical conductivity on temperature exhibits a thermally activated transport, which may be explained with grain boundary scattering.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 However, the crucial role in determining thermoelectric properties played by the unique nature of the graphite lattice in providing a multitude of boron substitutional configurations each with its distinctive energy signature appears to have been explicitly recognized for the first time in our earlier work. 4 This recognition led us to examine in detail the nature of the acceptorlike feature using density functional calculations on boron substituted polyaromatics that serve as molecular models for finite as well as stacked graphene sheets. 18 These calculations provide insight into the relative stabilities of high spin versus low spin states as a function of graphene sheet size, Kekule versus non-Kekule structures, as well as the effects on orbital energetics of various boron substitutional configurations.…”
Section: Discussionmentioning
confidence: 99%
“…It is for this reason that carbon and, in particular, boron doped nanocarbons were chosen as model systems for studies of their thermoelectric performance characteristics. 4 In that earlier work it was shown that reaction of disperse ultrananocrystalline diamond ͑UNCD͒ and mixtures of UNCD with 10%-20% nano-boron-carbide ͑B 4 C͒ with methane gas at temperatures near 1200 K results in mechanically rigid compacts called nanocarbon ensembles and boron doped nanocarbon ensembles, respectively. It needs to be understood that the amount of boron that enters into a substitutional solid solution in the nanocarbon ensembles as a dopant is only a small fraction of the quantity added initially.…”
Section: Thermoelectric Power Factors Of Nanocarbon Ensembles As a Fumentioning
confidence: 99%
See 1 more Smart Citation